Towards an informed research agenda for the field of personality disorders by experts with lived and living experience and researchers - Renneberg, Babette; Hutsebaut, Joost; Berens, Ann; De Panfilis, Chiara; Bertsch, Katja; Kaera, Andres; Kramer, Ueli; Schmahl, Christian; Swales, Michaela; Taubner, Svenja; Alvarez, Mariana Mendoza; Sieg, Julia (Borderline Personality Disorder and Emotion Dysregulation, 2024)
We describe a collection of themes for a research agenda for personality disorders that was originally formulated for the ESSPD Borderline Congress in 2022. Experts with lived and living experience (EE), researchers and clinicians met virtually, exchanged ideas and discussed research topics for the field of personality disorders. The experts - patients, relatives, significant others - named the topics they thought most relevant for further research in the field. These topics were presented at the ESPPD conference in October 2022. The five top themes were: 1. Prevention, early detection and intervention, 2. Recovery beyond symptom improvement, 3. Involvement of relatives in treatment, 4. Gender dysphoria, and 5. Stigma. In general, the topics reflect current issues and changes in societal values. Overarching aims of research on these topics are the improvement of social participation and integration in society, better dissemination of research, and better information of the general public and political stakeholders.
Gesehen am 06.02.2025